Transformation of Reward Systems to Enhance Employee Engagement in the Digital Platform Work Environment: A Literature Review: Transformasi Sistem Insentif untuk Meningkatkan Keterlibatan Karyawan dalam Lingkungan Kerja Platform Digital: Tinjauan Literatur - Dallia Alvi Nuro; Kukuh Harianto (Universitas Muhammadiyah Sidoarjo, 2025)
The transformation of reward systems in the digital work era has become a strategic issue in human resource management. Reward systems are crucial not only as tools of appreciation but also as key mechanisms for building motivation, emotional attachment, and employee loyalty, which ultimately impact organizational performance improvement. This study aims to analyze the contribution of reward systems, both intrinsic and extrinsic to enhance employee engagement in digital platform-based work. Using a literature review method with a descriptive qualitative approach, data collection was conducted through systematic searches and in-depth analysis of relevant scientific literature from journals, books, and trusted articles published. This review examines the forms of rewards, their effectiveness, digital transformation, as well as mediating and moderating factors that influence employee engagement. The findings indicate that fair, personalized, and technology-based rewards significantly increase motivation, loyalty, and employees’ emotional attachment. Digitalization enables reward systems to become more adaptive and relevant to the needs of modern workers. The implications of this study emphasize the importance of a humanistic and contextual HR management strategy to address the challenges of a flexible and digitalized work environment.